Overview Of SEFT Therapy (Spiritual Emotional Freedom Technique) On Reducing Anxiety Of III Trimester Pregnant Women At Oesapa Health Center - Abdullah, Mahaldi Wahyu; Mandala, Alin Dhayu; Kapitan, Meiyeriance; Kleden, Simon Sani; Namuwali, Domianus (Sean Institute, 2024)
Anxiety during pregnancy negatively impacts women from pregnancy to delivery, potentially leading to premature birth and miscarriage. Data from the Kupang City Health Service shows that in 2022, the number of pregnant women in the third trimester at the Oesapa Community Health Center was 1,410. Anxiety can be alleviated through various non-pharmacological therapies, one of which is the Spiritual Emotional Freedom Technique (SEFT) therapy. SEFT is a healing method that combines psychological energy with prayer and spirituality. This research aims to identify the effectiveness of SEFT therapy in reducing anxiety in third trimester pregnant women at the Oesapa Community Health Center. The study is quantitative, using a pre-experimental design with a one-group pre-posttest design. This involves three steps: administering a pretest to measure the dependent variable before treatment, providing experimental treatment to the subjects, and administering a posttest to measure the dependent variable after treatment. The statistical analysis results indicate that there are 44 negative ranks, meaning all 30 patients showed a decrease in anxiety levels before and after receiving SEFT therapy, with a mean rank or average decrease of 15.50. The sum of ranks is 465.00. The positive ranking results show no increase in anxiety levels in third trimester pregnant women before and after SEFT therapy, with a value of 0 for the N value, Mean rank, and Sum rank. This suggests that SEFT therapy is effective in reducing anxiety in pregnant women during the third trimester.